Future irrigation water demand and on-farm water conservation in England - Weatherhead, E. K. (Cranfield University, 2001)
The aim of this thesis is to predict the future demand for water for irrigation of outdoor agricultural crops in England, and to assess the likely on-farm responses to potential water shortages and related legislative change. The past underlying growth in the demand for irrigation water was assessed, by regression analyses of the MAFF irrigation survey results, for each of eight crop categories and in total, using modelled irrigation need as a proxy for climate variation. The growth in total water demand was validated by comparison with the reported growth in total abstractions. These indicate an underlying growth in total irrigation water use between 1982 and 1995 of between 3% and 4% per annum, expressed as percentages of the 1995 values. The results show that irrigation has been increasingly concentrated on the more valuable crops, notably maincrop potatoes, small fruit and vegetables, and that those crops that are irrigated have been increasingly given more water. The future growth in the demand for irrigation water, for each of the eight crop categories and- in total, was modelled as the product of predicted future crop areas, proportions to be irrigated, depths of water to be applied and application efficiencies. On-farm economic modelling, macro-economic models, and expert opinion were used to predict future changes in each of these factors. A spreadsheet model was then used to calculate the future growth in irrigation water demand, for each crop category and in total, and for each Region and nationally. The same methodology has also been applied within a GIS to map the spatial variation in growth. In later work, the Foresight scenario approach has been used to consider alternative socio- economic futures. These results predict that in the short to medium term at least, the total demand for irrigation water will continue to grow rapidly, and its use will become even more concentrated on the high-value crops. Growth is greatest in those areas where water resources are already most scarce. Meanwhile, water availability for agriculture is expected to be constrained or even decline because of increased environmental protection, particularly in the drier parts of the country where irrigation is concentrated. Climate change has not been modelled in this work, but under current predictions, it is likely to have a double effect, simultaneously reducing water supply and increasing water demand, and hence increasing the scarcity and value of water and the benefits of water conservation. The farmers' likely responses to the almost inevitable water shortages have been assessed by estimating the net on-farm value of the water, and comparing this to the benefits and costs of the various options for either reducing demand or increasing on-farm supply, within likely technical, legal and other constraints. The aspects considered include irrigation methods, scheduling, agronomic practices, mulches, on-farm reservoirs, water harvesting and water re- use. This analysis shows that the on-farm benefits of irrigation are generally substantially higher than the direct costs of irrigation. The benefits of conserving water are highly variable, partly because inflexible licensing restricts opportunities to reallocate water between farms. The thesis shows that on those farms where water is valuable and scarce, this will lead to on-farm investment particularly in on-farm reservoirs, more advanced technology and better scheduling. Constraints to change are discussed. Meanwhile, on farms which already have adequate water resources, there is at present little financial incentive to adopt any irrigation water conservation measures at all. The thesis concludes that both farmers and water regulators must prepare for a less certain future in which water for irrigation is scarcer and more valuable, and demand is higher and more concentrated. The opportunities for action by various groups are discussed.